MODERASI BERAGAMA SEBAGAI WUJUD AKTUALISASI IMAN DAN IHSAN DALAM KEHIDUPAN SOSIAL - Siregar, Sunggul Lelo; Wirman, Wirman; Katimin, Katimin; Aminuddin, Aminuddin (UIN Sumatera Utara Medan, 2026)
Religious moderation is an essential effort to maintain balance in religious life within a plural and multicultural society. This concept is rooted in the values of iman (faith) and ihsan (excellence in character), which emphasize steadfast belief, sincerity, and noble ethics in social interaction. Religious moderation is not merely a compromise, but a manifestation of strong faith and ihsan that upholds compassion, tolerance, and justice. In social life, religious moderation emerges as a solution to avoid extremism, intolerance, and radicalism, while at the same time fostering harmony and social cohesion. The actualization of iman and ihsan through religious moderation affirms that religion not only regulates the vertical relationship between humans and God but also the horizontal relationship among fellow human beings. Thus, religious moderation becomes the middle path that enables believers to practice their faith firmly while also upholding universal human values. This study aims to emphasize the urgency of religious moderation as a moral and ethical foundation in society, as well as a concrete manifestation of iman and ihsan in a dynamic social context.